KEMAMPUAN DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) DALAM MELARUTKAN BATU GINJAL KALSIUM - Komalasari, Oom; Iskandar, Yoppi; Wardojo, Moelyono Moekti (Publikasi Penelitian Terapan dan Kebijakan, 2014)
Binahong (Anredera cordifolia) leaves are used as medicine of kidney stones by society of Ogan Komering Ulu, but the ability to dissolve kidney stones clinically unproven yet. The study aimed to obtain information about capabilities of ethanol extract and fractions from Binahong leaves to dissolve kidney stones. Binahong leaves extract obtained by maceration using ethanol 96%, and then fractionated to obtain n-hexane fraction, ethyl acetate fraction and water fraction. Each of the fractions and extracts was dissolved in 10 mL aquadest with various concentrations of 2%, 4% and 8% referred as the testing solvent. A total of 100 mg of calcium kidney stone powder with particle size of 60/80 was soaked in the testing solvent then it was incubated at 37Â°C for 5 hours while stirring for 1 minute in every 1 hour. Level of dissolved calcium kidney stones in testing solvent was determined by using Atomic Absorption Spectrophotometry method at a wavelength of 422.7 nm. The research result showed that the average of the lowest solubility of calcium kidney stone was in concentration of 2% from extract, n-hexane fraction, ethyl acetate fraction and water fraction which were 2.83 mg/L; 2.02 mg/L; 2.67 mg/L and 7.19 mg/L,while the highest solubility was in concentration of 8% from extract, n-hexane fraction, ethyl acetate fraction and water fraction which were 5.87 mg/L; 3.72 mg/L; 5.25 mg/L; 9.22 mg/L. Based on the analysis of calcium levels using SPSS 19 with 2-way ANOVA method, there was significant difference of each treatment in dissolving calcium because p < 0.05 on trust level 95%. Water fraction had the best ability to dissolve calcium kidney stone, followed by extract and fraction of ethyl acetat and fraction of n-hexane.